2007
DOI: 10.1021/jf070978g
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Anti-gatifloxacin Antibody and Development of an Indirect Competitive Enzyme-Linked Immunosorbent Assay for the Detection of Gatifloxacin Residue in Milk

Abstract: A polyclonal anti-gatifloxacin antibody has been prepared, and an indirect competitive enzyme-linked immunosorbent assay (cELISA) was developed on the basis of the antibody prepared for the first time. The antibody shows high sensitivity with an IC50 value of 2.6 ppb and excellent specificity with only a minor cross-reaction with lomefloxacin (3.0%) among common (fluoro)quinolones evaluated in this study. The high specificity of the antibody was explained by the molecular structures of related drugs by compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 28 publications
4
38
0
Order By: Relevance
“…Therefore, more and more organizations have issued maximum residue levels (MRLs) and withdrawal criterion for FQs. According to different food resources and drugs, the MRLs of FQs are set in a range of 30-1500 μg/kg (Lu et al, 2006;Zhao et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, more and more organizations have issued maximum residue levels (MRLs) and withdrawal criterion for FQs. According to different food resources and drugs, the MRLs of FQs are set in a range of 30-1500 μg/kg (Lu et al, 2006;Zhao et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Huet et al [21] suggested that substituent at position 7 is the governing structural factor determining the binding affinity of fluoroquinolone molecules to anti-norfloxacin antibody and antisarafloxacin antibody. The substituent at position 8 in the structure of gatifloxacin was also believed to be a contribution to the high specificity of anti-gatifloxacin antibody [28]. The importance of substitution at position 1 in fluoroquinolone structures for antibody binding has also been stressed previously [27,30].…”
Section: Specificitymentioning
confidence: 99%
“…Fortunately, the active carboxylic acid group presented at position 3 in the molecule of norfloxacin (Table 1) enables direct conjugation to a carrier protein [27]. BSA and OVA are among the most commonly used protein carriers [28]. An immunogen NFX-BSA and a coating antigen NFX-OVA were synthesized using the N-hydroxysuccinimide active ester method [25].…”
Section: Production and Characterization Of The Antibodymentioning
confidence: 99%
See 1 more Smart Citation
“…Immunoanalytical techniques have been reported to detect GAT by an enzyme-linked immunosorbent assay (ELISA) using ultraviolet (UV) or fluorescence absorbance as a quantitative parameter (Santoro et al, 2006;Zhao et al, 2007). In recent years, electrochemical immunoassays have attracted attention because of their excellent sensitivity, simplicity, inexpensive construction, suitability for mass production, and their variety of labels, including enzymes and electro-active molecules.…”
Section: Introductionmentioning
confidence: 99%